Regulation of Meiotic Prophase One in Mammalian Oocytes - Wang, Xiaoyi; Pepling, Melissa E. (Frontiers in Cell and Developmental Biology, 2021)
In female mammals, meiotic prophase one begins during fetal development. Oocytes transition through the prophase one substages consisting of leptotene, zygotene and pachytene, and are finally arrested at the diplotene substage, for months in mice and years in humans. After puberty, luteinizing hormone induces ovulation and meiotic resumption in a cohort of oocytes, driving the progression from meiotic prophase one to metaphase two. If fertilization occurs, the oocyte completes meiosis two followed by fusion with the sperm nucleus and preparation for zygotic divisions; otherwise, it is passed into the uterus and degenerates. Specifically in the mouse, oocytes enter meiosis at 13.5 days post coitum. As meiotic prophase one proceeds, chromosomes find their homologous partner, synapse, exchange genetic material between homologs and then begin to separate, remaining connected at recombination sites. At postnatal day 5, most of the oocytes have reached the late diplotene (or dictyate) substage of prophase one where they remain arrested until ovulation. This review focuses on events and mechanisms controlling the progression through meiotic prophase one, which include recombination, synapsis and control by signaling pathways. These events are prerequisites for proper chromosome segregation in meiotic divisions; and if they go awry, chromosomes mis-segregate resulting in aneuploidy. Therefore, elucidating the mechanisms regulating meiotic progression is important to provide a foundation for developing improved treatments of female infertility.